Proposed Family Business Leadership Transition Strategy At Pt Sma - Liana Aripin (Cerdika: Jurnal Ilmiah Indonesia, 2025)
Effective leadership transitions are critical to the continuity and stability of family businesses, especially during generational shifts, which often bring significant challenges in conflict management. PT SMA, a family-owned food manufacturer, recently experienced a leadership change from the founder to a younger, less experienced leader. This transition caused conflict among stakeholders due to inadequate succession planning and differing perspectives across generations. This study examines strategies to address these conflicts and challenges at PT SMA. Key conflict points identified during leadership transitions include adjustments in leadership style and strategic vision, which can have a negative impact on organizational performance. This study proposes a structured approach to effective conflict management, emphasizing the development of a clear succession plan, facilitating conflict resolution, aligning organizational culture, and effective change management. By implementing these strategies, PT SMA aims to achieve a smoother transition, minimize conflict, and promote organizational stability. The findings will provide valuable insights for PT SMA and similar family businesses on the success of transition management and its impact on continued success. This study highlights the need to address challenges such as employee turnover and strategic disagreements, which can lead to dissatisfaction among long-term employees. Ultimately, effective conflict management is critical for new leaders to navigate these challenges and ensure a successful leadership transition. focus and advise on effective change management.